Child monitoring system (Parent) - Nabillah, Saleh (2008)
Bluetooth technology allowed multiple devices to communicate with each other or one device could control and manage the other device wirelessly. The Child Monitoring System (Parent) is one of alarm system which is developed using Bluetooth technology to monitor child in a certain area which is about 20 meters radius from the parent. The system is developed due to many cases of missing kids that happen nowadays in our country. To develop the system, there are several things needed to be learned. They are about PIC microcontroller, Bluetooth module data transmission and reception and also the existence system proposed by the other researchers. The important things to do during developing the system are assembly of the hardware which contain Bluetooth module as the main component for data transmission and reception while liquid crystal display (LCD) and buzzer as the indicator for the status of the child. The PIC microcontroller is acted as a controller that is reprogrammable and got the most important features to communicate two Bluetooth which is Universal Asynchronous Receiver Transmitter (UART). The software used is Microcode Studio to write and compile the PICBASIC programming language. This system could assist the parent in keeping an eye for their child whenever needed without the need of any licence.